Design and Evaluation of a Culturally Responsive Flipbook E-Module on Quantities and Units for Improving Students’ Critical Thinking Skills - Ellianawati Ellianawati; Figi Anggun Yossindy; Bambang Subali; Suharto Linuwih; Lolly Jean C. Simbulas (FKIP Universitas Lampung, 2026)
This study reports the development and empirical evaluation of a culturally responsive flipbook e-module for teaching quantities and units in Indonesian senior secondary physics. Developed using the ADDIE framework and grounded in Culturally Responsive Teaching (CRT), the module integrates local measurement systems, mud, tala, lot, and deben, as epistemic resources for scientific reasoning. A quasi-experimental field trial involved 117 Grade 10 students across three intact classes: two experimental groups (digital: n = 41; print: n = 40) and one control group (conventional worksheets: n = 36). Expert validation confirmed strong content validity (Aiken’s V = 0.87), particularly in cultural authenticity and alignment with critical thinking constructs. Student surveys indicated high practicality (89.55%) and positive perceptions (85.75%), with learners highlighting how culturally familiar contexts, such as zakat unit analysis or land measurement using lots, enhanced relevance and cognitive engagement. To evaluate learning impact, a pretest–posttest design was implemented, with critical thinking measured via a validated open-response instrument. Analysis of covariance (ANCOVA), controlling for pretest scores, revealed a statistically significant effect of instructional modality on posttest performance, F(2, 113) = 58.34, p < 0.001, with a large effect size (partial η² = 0.513). Adjusted means showed that the experimental groups significantly outperformed the control group (Madj = 79.14 (digital); Madj = 80.72 (print); Madj = 42.13 (control); p < 0.001), while there was no meaningful difference between the delivery modes (p = 0.682). These findings suggest that the CRT-based design, rather than the medium, influences learning outcomes, supporting scalable implementation across diverse infrastructural contexts. When cultural knowledge is structurally integrated into disciplinary reasoning, students engage more deeply, affirming the module’s potential as an equitable, contextually relevant tool for improving rigorous science education. Keywords: critical thinking skills, e-module, culturally responsive teaching.